Perilaku Pengguna Angkutan Umum Perkotaan di Tangerang Selatan - Syafieq Fahlevi Almassawa; Nani Nani (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Communities in general are in urgent need of public transportation beside private vehicles as a means of supporting the transportation of daily activities to meet their needs. The problem in big cities in Indonesia is urban transportation, especially big cities that are crowded like in Jabodetabek. The increasing number of residents of South Tangerang city is 3.27% high and the increase of the number of both motorcycles and four wheels is not followed by the improvement of urban public transportation service quality. Communities also negatively assess public services, especially urban transport that makes them choose to use private vehicles that can cause problems lannya social problems plus the lack of regulation in the use of private vehicles. The purpose of this research is to examine and analyze the relationship of urban public transportation concept which influenced by service quality, perceived value and government regulation. The research method used is Structural Equation Modeling LISREL with population of urban transport passengers in south tangerang with 400 respondents. The result of this research shows that consumer behavior is influenced by service quality, perceived value an. And there is a positive mediation effect of service quality and perceived value on consumer behavior